2018
DOI: 10.1021/acssensors.8b00456
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Specific H2Sn Fluorogenic Probe for Live Cell Imaging by Rational Utilization of a Dual-Functional-Photocage Group

Abstract: Reactive sulfur species play a very important role in modulating neural signal transmission. Hydrogen polysulfides (H 2 S n , n > 1) are recently suggested to be the actual signaling molecules. There are still few spatiotemporal controllable-based probes to detect H 2 S n . In this work, for the first time, we proposed the photocleavage product of the common photoremovable protecting group (2-nitrophenyl moiety) capable of trapping H 2 S n . Taking advantage of this, we constructed the probe H1 containing a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Hence, discovery of potent multifunctional/“all-in-one” dyes, with lower tissue autofluorescence, light scattering and photon attenuation, is noteworthy in future photo based therapy (PTT, PDT, PA, etc.). Nowadays, various Janus-faced molecules in disease models have been discovered and their fluorogenic reactions are under development [ [81] , [82] , [83] ]. It is necessary to further enlarge trigger-tool boxes with high sensitivity and selectivity to stimulate future drug discovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, discovery of potent multifunctional/“all-in-one” dyes, with lower tissue autofluorescence, light scattering and photon attenuation, is noteworthy in future photo based therapy (PTT, PDT, PA, etc.). Nowadays, various Janus-faced molecules in disease models have been discovered and their fluorogenic reactions are under development [ [81] , [82] , [83] ]. It is necessary to further enlarge trigger-tool boxes with high sensitivity and selectivity to stimulate future drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, various Janus-faced molecules in disease models have been discovered and their fluorogenic reactions are under development [ [81] , [82] , [83] ]. It is necessary to further enlarge trigger-tool boxes with high sensitivity and selectivity to stimulate future drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent probe for persulfide and polysulfide using an aldehyde group. Han et al (35) have reported a photoactivatable and mitochondria-targeting fluorescent probe for hydrogen polysulfides, H1, utilizing an aldehyde group as the reaction site (Fig. 4F).…”
Section: Recent Developments In Fluorescent Probes For H 2 Smentioning
confidence: 99%
“…Hydrogenous polysulfides are actual signaling molecules with even higher nucleophilicity and reducibility than H 2 S [26]. The fluorescence probes for hydrogenous polysulfides achieved widespread applicability in recent studies [27,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence probes for hydrogenous polysulfides achieved widespread applicability in recent studies [27,28,29,30,31]. Some of these probes are even organelle-specific and thus able to selectively label and allow tracing sulfur compounds in mitochondria [26,32]. Moreover, it is possible to monitor, in real-time, variations in polysulfide cell content and/or in vivo [33].…”
Section: Introductionmentioning
confidence: 99%